Peran Guru, Keluarga, Dan Teman Sebaya Dalam Perilaku Gizi Remaja Di Masa Pandemi Covid 19 - Nourmayansa Vidya Anggraini; Serri Hutahaean; Rizki Amalia; Vionita Apriliana; Lutfi Riskyta Istikomah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:   Adolescents are part of the population who are in the age range of 10-18 years. Adolescents are vulnerable to nutritional problems. This is due to changes in lifestyle including consumption patterns that are influenced by the surrounding environment. the national prevalence of obesity in adolescents aged >18 years was 14.8% in 2013 and increased to 21.8% in 2018. This is influenced by various factors. friends of the same age. Methods:  This research was conducted at SMPN 5 Depok in July 2022 to 261 students in grades 7, 8, 9 using simple random sampling technique. The variables of this study consisted of the independent variables, namely the role of parents, teachers, and peers, while the dependent variable was the nutritional behavior of adolescents. Data was collected through the distribution of questionnaires. Statistical analysis was conducted to determine the relationship between parents, teachers, and peers on adolescent nutritional behavior in students at SMPN 5 Depok. Before the researcher carried out the research, he explained the research procedure to the sample and received approval from each sample. Results:   There is no relationship between the role of parents and peers with adolescent nutritional behavior. There is a relationship between the teacher's role and adolescent nutritional behavior. Conclusion:   Parents and teachers still need to supervise in matters relating to nutritional behavior in adolescents. Adolescents are more likely to follow the attitudes and behavior of their peers.